2018
DOI: 10.3390/molecules23061253
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Production Conditions for Protoplasts and Polyethylene Glycol-Mediated Transformation of Gaeumannomyces tritici

Abstract: Take-all, caused by Gaeumannomyces tritici, is one of the most important wheat root diseases worldwide, as it results in serious yield losses. In this study, G. tritici was transformed to express the hygromycin B phosphotransferase using a combined protoplast and polyethylene glycol (PEG)-mediated transformation technique. Based on a series of single-factor experimental results, three major factors—temperature, enzyme lysis time, and concentration of the lysing enzyme—were selected as the independent variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…We observed that the incubation of mycelia with lysing enzymes yielded 3.82 × 10 8 ± 0.86 × 10 8 protoplasts after 3 h, enough to perform around 20 transformation experiments. This value was estimated considering 1 × 10 7 protoplasts for each transformation experiment, amount optimal in most protocols of fungal PEG-mediated transformation (Liu and Friesen, 2012; Wang et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that the incubation of mycelia with lysing enzymes yielded 3.82 × 10 8 ± 0.86 × 10 8 protoplasts after 3 h, enough to perform around 20 transformation experiments. This value was estimated considering 1 × 10 7 protoplasts for each transformation experiment, amount optimal in most protocols of fungal PEG-mediated transformation (Liu and Friesen, 2012; Wang et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…For PEG-mediated transformation of fungi, researchers usually use DNA amounts ranging from 2 to 12 μg (Fincham, 1989; Wang et al, 2018). In our case, we tested three DNA amounts within this range (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The recombined silencing plasmid was designated as pSilent‐GtCytc 1 , purified, and transferred into the wild‐type strain using the PEG‐mediated transformation method according to Wang et al . (2018). The hairpin RNA silencing plasmids of GtCytb (387 bp) and GgIsp (389 bp) were constructed with the same strategy and verified by PCR with the primer pair PScheck 1F/R (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…The same fragment of GtCytc 1 was amplified with the primer pair FGtCytc 1 -F/R, purified, and inserted into the KpnI/SphI site of pSilent-GtCytc 1 -up ( Figure S2b). The recombined silencing plasmid was designated as pSilent-GtCytc 1 , purified, and transferred into the wild-type strain using the PEG-mediated transformation method according to Wang et al (2018). The hairpin RNA silencing plasmids of GtCytb 387 bpand GgIsp (389 bp) were constructed with the same strategy and verified by PCR with the primer pair PScheck 1F/R ( Figure S3).…”
Section: Construction Of Hairpin Rna Silencing and Overexpression Vmentioning
confidence: 99%
“…The currently used transient transformation method is polyethylene glycol (PEG)-mediated transient expression of protoplasts [11]. Effective mesophyll protoplast isolation, purification, and transient transformation systems have been established in many plant species, such as wheat [12], Arabidopsis thaliana [11], and Chinese kale [13]. Studies on plant hypocotyl protoplasts have focused on isolation, purification, and regeneration [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%